Gontor Putri Education: A Model for Character Formation of Prospective Students - Mafaza Salmi; Moh Alwi Yusron; Aisya Rahma El-Fani (Global Education Journal, 2026)
The development of moral character is a very important element in Islamic education, especially in Islamic boarding schools. This research focuses on the importance of moral development for the younger generation facing the challenges of globalization, where ethical values are often overlooked. Pondok Modern Darussalam Gontor Putri Campus 2 implements a character education and learning system to shape the personality of students, including for prospective new students in the 2025–2026 school year. This research was conducted to understand the education and learning process at Gontor Putri Campus 2 in shaping the character of morals for prospective students. The method used in this study is qualitative with a study design in the field. The subjects of this study are students who have the potential to become students at Gontor Putri Campus 2 for the 2025–2026 school year. Data was obtained through observation, interviews, and document collection, then analyzed using data grouping methods, data presentation, and specific facts identified at the location. The results of the study show that an education system that combines intracurricular, extracurricular, and daily habits plays an important role in the development of moral character for prospective students. Habituation of discipline, strengthening of religious values, and example provided by teachers and seniors are important factors that support this process. The implications of this study show that it is very important for the younger generation to have a solid moral foundation in facing the various challenges of the times.